Społeczne postrzeganie innowacji w krajach UE (na podstawie badań Eurobarometer) - Markowska, Małgorzata (Social Perception of Innovation in EU Member Countries (Based on Eurobarometer Research), 2008)
The article presents research results - carried out by Eurostat within the framework of the European Trend Chart on Innovation and Eurobarometer - regarding the attitudes of European citizens towards innovation as well as the assessment of the position of Poland among other EU countries with reference to innovation.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 2, s. 22-29